Antihyperglycemic Activity of Methanolic Extract of Scindapsus officinalis Root in Normal and Streptozotocin-Induced Diabetic Rats - Das, D.; Ghosh, G.; Badjena, L.; Dash, B. (Asian Journal of Chemistry, 2012)
The aim of this study is to evaluate the antihyperglycemic effect of methanolic extract of Scindapsus officinalis (MESO) in different models of rats. The antidiabetic activity was evaluated by oral administration of methanolic extract of Scindapsus officinalis at the doses of 200, 400 and 600 mg/kg using normal, glucose-loaded hyperglycemic and streptozotocin-induced diabetic rats. The effect of repeated oral administration of aqueous extract on serum lipid profile and plasma enzyme levels in diabetic rats was also examined. The three doses caused significant reduction in blood glucose levels in all the models. The effect was more pronounced in 400 and 600 mg/kg than 200 mg/kg. In oral glucose tolerance test, reduction of fasting blood glucose levels took place from 1 h of extract administration. The extracts produced a dose-dependent fall in fasting blood glucose. This dose showed almost similar effect as that of standard drug, glibenclamide (10 mg/kg bw). After 15 days of treatment with the extracts the maximum reduction in fasting blood glucose (54.25 %) was observed in diabetic rats treated with methanolic extract at a dose of 600 mg/kg. Total cholesterol, low density lipoprotein and triglyceride levels were decreased by 32, 72 and 25 %, respectively in diabetic rats, whereas, cardioprotective, high density lipoprotein was increased by 16 %. Methanolic extract of Scindapsus officinalis also restored the altered plasma enzyme (aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase) levels to near normal. These results clearly indicate that methanolic extract of Scindapsus officinalis possess high antihyperglycaemic potential along with significant hypolipidemic properties.